Effects of a Preseason Neuromuscular Training Program vs. an Endurance-Dominated Program on Physical Fitness and Injury Prevention in Female Soccer Players - Ali Belamjahad; Claire Tourny; Nidhal Jebabli; Cain C. T. Clark; Ismail Laher; Anthony C. Hackney; Urs Granacher; Hassane Zouhal (SpringerOpen, 2024)
Abstract Background The pre-season preparatory period is considered key for optimizing the physical fitness levels needed to withstand congested match periods and preventing injuries during the regular soccer season. This study contrasted the effects s of neuromuscular training (NMT) versus an endurance-dominated training (ET) program conducted during the preseason on measures of physical fitness and injury occurrence in female soccer players. Methods Twenty-four female soccer players aged 17.0 ± 1.3 years from a professional soccer club participated in this study. Players were randomly assigned to NMT (n = 12) or ET (n = 12) groups according to their playing position. The preseason intervention program lasted six weeks, with three weekly sessions with a duration of 45-60 min per session. Exercises in the NMT group included muscle strengthening exercises, plyometrics, agility and dynamic stability exercises, while the ET group practiced a traditional pre-season training program consisting of running and sprinting exercises, fartlek, and high-intensity interval training. The training volumes were similar in the two study groups. Anthropometric measurements, physical fitness tests (i.e., linear and change-of-direction speed, muscle strength and power tests) and the overall injury rate per 1000 h of exposure (training, match) were recorded throughout the season. Results No between group differences were found at pre (T1). Significant group-by-time interactions were observed for the 5, 10, and 30-m linear sprint speed tests (p < 0.001, 2.16 < d < 2.58), the T-test (p = 0.024, d = 1.03), the squat (p < 0.001, d = 4.04), and the countermovement jump test (p < 0.001, d = 2.21), the Loughborough soccer passing test (LSPT) (p = 0.019, d = 1.08), and the 1-RM back squat test (p < 0.001, d = 2.53). Post-hoc tests indicated that NMT provided larger improvements for SJ, CMJ, 1-RM back squat, the 5-m sprint, 10-m sprint, 30-m sprint, T-test and LSPT compared to ET (1.07 > d > 2.77). The injury rate across the season was significantly lower in the NMT (5.1/1000 h exposure) compared to ET (11.8/1000 h exposure) (p = 0.014). Conclusions The findings support that six-weeks of preseason NMT versus ET induced larger performance improvements, and significantly reduced injury occurrence in elite female soccer players.